Generalized Extreme Value Distribution for Modeling Earthquake Risk in Makran Subduction Zone Using Extreme Value Theory - Adil Rehman; Huai Zhang (Indonesian Journal of Earth Sciences, 2023)
The long-term pattern of severe incidents is one of the most crucial and fascinating topics of seismic events. This work aims to analyze the maximum annual earthquake magnitude in the Makran subduction zone using extreme value theory by implementing the block maxima method. The seismic data utilized for the current study was collected from the International Seismological Center (ISC) ranging from 1934 to 2022. The extreme parameters have fitted utilizing the generalized extreme value distribution. Numerous plots of the generalized extreme value distribution approach gave the accuracy of the used model when fitted to seismic data of the Makran subduction zone. Using the profile likelihood approach, the shape parameters (?) calculated is 0.29. According to the model fit, the Fréchet distribution is the best model for predicting the annual maximum earthquake magnitude in the Makran subduction zone. The estimated return levels for different return periods 10, 20, 50, and 100 are 6.35, 6.81, 7.58, and 8.31, respectively, indicating that an earthquake's maximum magnitude is increasing across the future 100 years. We also computed the profile likelihood to achieve a precise confidence interval. Thus, the 1945 earthquake of the Makran region with magnitude 8.1(Mw) was one of the most significant events in this area and occurred once every 100 years. The significance of this research is to inform decision-makers to implement suitable risk-mitigation methods.